Free radical-assisted electrocoagulation processes for wastewater treatment - Al-Qodah, Z; Al-Shannag, M; Bani-Melhem, K; Assirey, E; Yahya, MA; Al-Shawabkeh, A (Springer Heidelberg, 2024)
The combination of electrocoagulation with another process is a promising approach to enhance the removal efficiency of water pollutants. For instance, free radical-assisted electrocoagulation is a new combination showing higher performance. There are different combinations depending on the free radical source. This article reviews free radical-assisted electrocoagulation processes. We discuss electrocoagulation mechanisms; ozone-assisted electrocoagulation processes; advanced oxidation-assisted electrocoagulation processes; and ultrasound-assisted electrocoagulation. We present kinetic models used in free radical-assisted electrocoagulation, scale-up of free radical-assisted electrocoagulation and cost estimation. The major points are: most of the available studies have been done at laboratory scale with synthetic wastewater, and lack holistic and systematic approaches to consider the process complexity. The performance of the combined process is improved, and the removal efficiency is increased especially with ozone-assisted electrocoagulation, which gives a removal efficiency of more than 95%. The use of ultrasound energy with electrocoagulation is advantageous in reducing the problem of electrode passivation.